1993
DOI: 10.1159/000111324
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Forelimb Amputation Affects Protein Synthesis in Ipsilateral and Contralateral Spinal Cord and Spinal Ganglia Neurons of the Newt in vivo

Abstract: The aim of this investigation was to analyze the effect of urodele limb amputation and blastema growth on the protein synthesis in spinal cord and spinal ganglia neurons corresponding to the 3rd and 4th spinal segment of young, postmetamorphic Triturus vulgaris, in vivo. Protein synthesis was studied on both trunk sides as a function of right forelimb amputation at the distal stylopodium, and blastema development, during a critical period of 22 days post amputation (dpa). Protein synthesis was assessed by coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Soon thereafter it was revealed that spinal ganglia might play a leading role in the latter process [Walter, 1919]. Numerous investigations have since been performed in the hope that elucidation of the cellular and molecular parameters in-volved might be used profitably at the clinical level [Anton and Koussoulakos, 1993;Tong et al, 1998]. …”
Section: Resultsmentioning
confidence: 99%
“…Soon thereafter it was revealed that spinal ganglia might play a leading role in the latter process [Walter, 1919]. Numerous investigations have since been performed in the hope that elucidation of the cellular and molecular parameters in-volved might be used profitably at the clinical level [Anton and Koussoulakos, 1993;Tong et al, 1998]. …”
Section: Resultsmentioning
confidence: 99%